Recurrence of Löfgren’s syndrome 32 years later. A case report and review of the literature - Iriarte, Adriana; Rubio-Rivas, Manuel; Corbella, Xavier; Mañá, Juan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Not available